Factors influencing the decision to use epidural anesthesia for women - Maria Josefa Campoy Quesada; Juan Pedro De Haro García (Universidad de Alicante, 2014)
Justification: Immigration in Spain is a very important phenomenon which reverberates in the field of the health. Objective: To investigate the relation between the choice of epidural anesthesia and the nationality of the women, and in turn, to observe if other factors also influence this decision. Design and Methodology: Quantitative, cross-sectional and descriptive study of 634 women who have given birth at the Northwestern Hospital in the Region of Murcia. The variables selected were: obstetric history, age, type of anesthesia, the nationality of women and reasons of rejection of epidural anesthesia. Results: The 8, 51% of women who have given birth in the Northwestern Hospital in the Region of Murcia in 2010 were immigrants. As for nationality, 20, 37% of women immigrants have not used any type of anesthesia. We found a significant difference with the Spanish immigrant women in which only 4, 31% rejected (P< 0,001). In relation to abortions, women who do not prefer any anesthesia are those who do have abortions (P<0, 05). Younger ages for women, 16 to 25 years, is associated with no use of epidural anesthesia (P<0, 05). Conclusion: Immigrant women make less use of epidural anesthesia. It is a challenge for nurses to learn the different cultures and to carry out work in an increasingly multicultural society.